Deformation Stability and Failure Analysis of Composite Interface Accumulation Slope - LI Shuai (Renmin Zhujiang)
Distribution of groundwater and accumulated soil stress is an important factor for the deformation stability and failure mode of composite interface slope.Based on the typical geological section of Dongjiashan landslide,this paper generalizes a geomechanical model of composite interface slope,analyzes the development and evolution results of the equivalent plastic zone of the slope at different groundwater levels by finite element software,mainly explains the stress and deformation characteristics of the slope,slip zone and central soil in natural state,and reveals the deformation and failure mechanism of the composite interface slope.The numerical calculation results show that under natural and heavy rain conditions,the equivalent plastic zone of the slope first penetrates integrally and gradually develops towards the middle of the slope,and finally forms the secondary plastic penetrating surface in the upper middle part of the slope.The groundwater level reduces the stability of the composite base slope,and there is a higher possibility of secondary sliding on the upper part of composite interface slope during heavy rain.The shape of the horizontal displacement change curve of the slip zone and slope is similar to that of the composite interface,and the non-monotonic change potential slip surface affects the deformation distribution and failure mode of the slope at the geotechnical composite interface.